Скляні вироби з розкопу ХІІ на території Меджибізької фортеці у 2015 р. - Толкачов, Ю.І.; Журухіна, О.Ю. (Археологія і давня історія України, 2018)
Cтаття присвячена виробам зі скла, виявленим
під час археологічних розкопок на території Меджибізької фортеці у 2015 р. Це посуд, прикраси та
віконне скло від давньоруських до пізніших часів. Excavations conducted on the territory of the
Medzhybozh Fortress in 2015, explored the cultural
layer, in which among various archaeological material
were found objects of glass. Finds are divided into three
categories: vessels, jewelry, and decor elements. Most of
them are jewelry: the bracelets and beads. The vessels,
beads, and bracelets, according to their morphology and
technology, have Ancient Rus’ origin. Some of the bracelets
were produced in Byzantium. The fragments of the
window glass belong, probably, to the later period.